What is behind the location decision for a MNE from an emerging market? The case of Huawei Company - Pollicino, D. (2016)
There is a general agreement that BRICS appear to become the largest global economy group. China became the most developed country among developing countries. Furthermore, a huge amount of Chinese companies increased and started to keep eyes on the overseas market to acquire more market share, develop the brand and become a pioneer of the industry in which the firm is embedded. Huawei Company after many years became the pioneer of the Chinese high-tech world. The process of internationalisation has been affected by the factors and the decision making of location. This paper aims to provide information about factors behind the choice of location when firms from developing country want to expand overseas. The paper concludes that factors behind the choice of location are different and that it seems to be favourable to expand into developed countries rather than developing.